Classification of forest vegetation in Yaraligöz Education and Observation Forest, Kastamonu, Türkiye - MUSTAFA KARAKÖSE; SALIH TERZIOĞLU (Nusantara Bioscience, 2023)
Abstract. Karaköse M, Terzioglu S. 2023. Classification of forest vegetation in Yaraligöz Education and Observation Forest, Kastamonu, Türkiye. Nusantara Bioscience 15: 161-171. Forest ecosystems, which contain approximately half of the 12,975 plant taxa known to be distributed in Türkiye, are very important in terms of biological diversity. The fact that forests are seen as wood-producing ecosystems and have been planned for these purposes for many years has resulted in forests being kept away from being evaluated in terms of ecosystem and socio-economic aspects. Today, forest management plans have begun to be prepared in which all components of the forest are considered, and biological diversity is reflected. Based on this understanding, this investigation was performed during 2011-2012 to analyze the forest vegetation of Yaraligöz Education and Observation Forest. The study area is located in the north-western part of Türkiye within the Euro-Siberian phytogeographic region. Phytosociological studies were carried out using the classical Braun-Blanquet approach, and 51 relevés were collected from the research area. The database contains 184 vascular plant taxa, dominated by the Euro-Siberian elements and Hemicryptophytes. The relevés were classified using the Modified TWINSPAN, and the forest vegetation types' distribution was analyzed using non-metric multi-dimensional scaling. A comprehensive comparison among all described syntaxa within the study area and other closely related forests was provided. Topographic factors and mean Ellenberg indicator values were evaluated to interpret the ecological relationships among forest plant associations. Four associations, two (Daphno pontica-Pinetum hamatae and Galio rotundifolii-Abietum equi-trojani) of which are new syntaxa to science, were defined as belonging to the Euxine Province within Erico-Pinetea, Carpino-Fagetea sylvaticae, Quercetea pubescentis, and Vaccinio-Piceetea. The distribution of these four forest associations was mostly affected by light intensity, nutrients, moisture content, and altitude. The results of this vegetation study provided precious knowledge for monitoring vegetation change and nature conservation projects in the Yaraligöz.